Fifteen-year evaluation of the influence of mechanical pruning on olive yield - Dias, António B. (2015)
In Portugal, olive (Olea europaea L.) groves with the traditional tree density of around 100 trees ha -1 require an urgent reduction in production costs in order to survive. This requirement becomes imperative at the present state of low prices of olive oil in the world market. The authors have been studying, since 1997, a mechanised alternative to the expensive and labour intensive manual pruning practice (Dias et al., 2012), (Dias et al., 2008), (Peça et al., 2002). Three treatments were followed in field trials:T1 - manual pruning with a chain saw, performed in 1997, 2006 and 2011;T2 - mechanical pruning, performed by a tractor mounted cutting bar provided with 6 circular disc-saws, in 1997, 2006 and 2011. In 2011 the mechanical pruning was followed by a manual pruning complement to eliminate the great diameter suckers from the central part of the canopy; T3 - mechanical pruning, as in T2, followed by a manual pruning complement in 1997, 2006 and 2011. In 1997 and 2011 the manual pruning complement was done immediately after the mechanical pruning. In 2006 only mechanical pruning was done and the manual pruning complement intervention was done in the following year (2007). The effect of the above treatments on olive yield was evaluated at an annual basis for 15 years. The main results showed that over the first 9 years period mechanical pruning (T2) revealed a higher accumulated yield. However, over the following 6 years period, the yield obtained by the mechanical pruning treatment (T2) was a lower than the yield of the other two treatments, which showed to be similar. Following this results a pruning strategy was put forward based on mechanical pruning, complemented by manual pruning. The manual pruning complement should always be evaluated on a case by case basis, although this study points that it could be performed after the second or third mechanical pruning intervention.